Pengaruh Model Pembelajaran Induktif terhadap Kemampuan Pemahaman Konsep Matematika Siswa Sekolah Dasar - Tuhu Setyono; Wiwid Satriyo (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to describe the effect of the inductive learning model on the ability to understand mathematical concepts of elementary school students. The research method used is a quasi-experimental research method. Quasi-experimental design used pre-test post-test. The research population was 50 students. The research sample consisted of 28 students with 14 students in the experimental class composition in elementary school A and 14 students in the control class in elementary school B. The data collection technique used was to measure students' ability to understand mathematical concepts. The research instrument used was a test sheet for the ability to understand students' mathematical concepts. The data analysis technique was carried out using quantitative data analysis techniques. The results showed that the ability to understand mathematical concepts of the group of students who used the inductive learning model in elementary school A was higher than the ability to understand mathematical concepts of the control group in elementary school B. The inductive learning model had a significant effect on the ability to understand mathematical concepts of students in elementary school A. Learning model inductive reasoning must continue to be applied by the teacher so that the understandings of other students can develop optimally.